Influence of thin film properties on the electrochemical performance of diamond electrodes - Hian, L; Grehan, K; Compton, R; Foord, J; Marken, F (2003)
The electrochemical properties of nanocrystalline diamond films grown by microwave-enhanced chemical vapour deposition from a helium-hydrogen-methane gas phase mixture on Ti substrates are explored. A range of important redox systems are examined in aqueous solution including the oxidation of hydroquinone and ascorbic acid, and the electrodeposition and stripping of Au and Cu. Compared to boron-doped diamond materials, the nanodiamond is found to be a highly active electrode material, with low overpotentials and high adherence of metallic electrodeposits, for the redox systems studied. © 2002 Elsevier Science B.V. All rights reserved.